2021
DOI: 10.1177/0300060521997745
|View full text |Cite
|
Sign up to set email alerts
|

Combined pulsed-dye laser and medical therapy for treatment of cutaneous sarcoidosis lesions: a case report

Abstract: Sarcoidosis is a systemic granulomatous disease of unknown etiology that most frequently occurs in the lungs. However, cutaneous lesions are often the primary sign. Cutaneous sarcoidosis is difficult to treat, although different therapies have been applied. We herein report a case in which cutaneous sarcoidosis was treated with pulsed-dye laser (PDL) therapy along with oral administration of acitretin and hydroxychloroquine; no topical medications were applied. All patient details are de-identified. The treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While the existing literature discusses the treatment of cutaneous sarcoidosis with laser therapy [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] ( Table 1 ), there are also singular occurrences describing laser therapy causing cutaneous sarcoidosis [ 36 , 37 ] ( Table 2 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…While the existing literature discusses the treatment of cutaneous sarcoidosis with laser therapy [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] ( Table 1 ), there are also singular occurrences describing laser therapy causing cutaneous sarcoidosis [ 36 , 37 ] ( Table 2 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Dong et al [ 25 ] reported a 46-year-old Asian woman with longstanding left facial lesions, diagnosed with cutaneous sarcoidosis. Treatment included acitretin (10 mg q.d.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Pulsed solid‐state lasers operated at around 2 µm range to have great significance for the absorption peak of water molecules and human issue which have many application including laser lidar, 1,2 optoelectrionic countermeasure, 3–7 laser minimally invasive surgery, 8 and environmental monitoring, 9 and so on. In addition, 2 µm pulsed lasers are efficient pump sources for nonlinear optical frequency conversion in the range of 3–12 µm 10,11 .…”
Section: Introductionmentioning
confidence: 99%